Clinical mentorship of midwifery students: The perceptions of registered midwives - Hafaza B. Amod; Lindani Ndlovu; Petra Brysiewicz (AOSIS, 2024)
Background: Clinical mentors are experienced practitioners who play an important role in encouraging the professional development of students in clinical areas. The responsibility of clinical mentorship in nursing is often difficult to maintain. However, there is a dire need for clinical mentorship in maternity units, especially in South African hospitals were high maternal mortality rates remain alarmingly high. Aim: This study aimed to describe the perceptions of registered midwives regarding the clinical mentorship of midwifery students. Setting: The study occurred in a semi-rural state regional hospital in the eThekwini district, KwaZulu-Natal. Methods: A qualitative exploratory and descriptive design was conducted using in-depth individual interviews with midwives in maternity units. A purposive and convenient sampling method recruited 17 registered midwives from 3 maternity care areas within a single setting. Interviews were audio-recorded and all data were analysed using qualitative content analysis. Results: Five categories emanated from this study namely, sharing knowledge and skills; encouraging role model behaviour; promoting self-worth; Is a challenging task; and requiring additional support. Conclusion: Clinical mentorship has a reciprocal effect on teaching and learning in maternity care areas and encouraged registered midwives to lead as role-models. The process demands competence, professionalism, and leading by example. Despite the confidence, satisfaction and interest in clinical mentorship, registered midwives often find the process challenged by patient care priorities. Therefore, registered midwives require additional support to mentor students in clinical practice. Contribution: This article shows that clinical mentorship places various challenges on registered midwives and formal mentorship training could be beneficial.